Bilateral coronoidectomy, the panacea for trismus-sequel of post op radiotherapy: a case report - Munjal, Manish; Munjal, Shubham; Chauhan, Swati; Arora, Vineeta; Gupta, Varun; Singla, Sanjiv; Sidhu, Majinder; Jeriwal, Sakshi; Bharadwaj, Prachee; Juneja, Keshav; Pillai, Anjana (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Trismus is the untoward sequel of the radio therapeutic modality incorporated in head and neck malignancy. The restricted mouth opening progresses gradually leading to reduced oral intake and thereby a markedly debilitated individual. Oral exercises, dilatational devices and masticatory apparatus surgical interventions are undertaken as the case maybe.